Persepsi Mahasiswa Terhadap Respons Komunikasi DANA Atas Isu Saldo Hilang Tahun 2024 Dalam Konteks Cancel Culture Di Media Sosial - Camelia Sa’adah; Rina Juwita; Kezia Arum Sary; Ziya Ibrizah (CV. Global Cendekia Inti, 2026)
The rapid growth of social media has transformed crisis communication by enabling the public to quickly shape and disseminate opinions about organizations. This development presents significant challenges for financial technology (fintech) companies, including DANA, during the 2024 missing balance issue that attracted widespread public attention on social media. This study aims to analyze university students' perceptions of DANA's crisis communication response using the Situational Crisis Communication Theory (SCCT) framework. A qualitative approach with a case study design was employed. Informants were selected through purposive sampling, while data were collected through in-depth interviews and document analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings reveal that students' perceptions were primarily influenced by the timeliness of the company's response, information transparency, message consistency, and organizational empathy throughout the crisis. Perception formation was also shaped by social experiences, interpersonal communication, social media exposure, and digital literacy. Furthermore, cancel culture emerged as a form of social evaluation reflected in declining public trust, increased user caution, and the widespread dissemination of negative opinions toward the organization rather than a complete boycott. This study extends the application of SCCT by demonstrating that organizational responsibility attribution in the digital era is constructed through the interaction between corporate crisis communication strategies and the dynamics of social media communication. The findings highlight the importance of responsive, transparent, dialogic, and adaptive crisis communication strategies for fintech companies to maintain public trust and protect organizational reputation.